Sustained benefit of cognitive behaviour therapy for health anxiety in medical patients (CHAMP) over 8 years: a randomised-controlled trial. Issue 10 (16th July 2021) - Tyrer, P.; Wang, D.; Crawford, M.; Dupont, S.; Cooper, S.; Nourmand, S.; Lazarevic, V.; Philip, A.; Tyrer, H.
Abstract: Background: Health anxiety is an under-recognised but a frequent cause of distress. It is particularly common in general hospitals. Methods: We carried out an 8-year follow-up of medical out-patients with health anxiety (hypochondriasis) enrolled in a randomised-controlled trial in five general hospitals in London, Middlesex and Nottinghamshire. Randomisation was to a mean of six sessions of cognitive behaviour therapy adapted for health anxiety (CBT-HA) or to standard care in the clinics. The primary outcome was a change in score on the Short Health Anxiety Inventory, with generalised anxiety and depression as secondary outcomes. Of 444 patients aged 16–75 years seen in cardiology, endocrinology, gastroenterology, neurology and respiratory medicine clinics, 306 (68.9%) were followed-up 8 years after randomisation, including 36 who had died. The study is registered with controlled-trials.com, ISRCTN14565822. Results: There was a significant difference in the HAI score in favour of CBT-HA over standard care after 8 years [1.83, 95% confidence interval (CI) 0.25–3.40, p = 0.023], between group differences in generalised anxiety were less (0.54, 95% CI −0.29 to 1.36), p = 0.20, ns), but those for depression were greater at 8 years (1.22, 95% CI 0.42–2.01, p < 0.003) in CBT-HA than in standard care, most in standard care satisfying the criteria for clinical depression. Those seen by nurse therapists and in cardiology and gastrointestinal clinics achieved the greatest gains with CBT-HA, with greater improvement in both symptoms and social function. Conclusions: CBT-HA is a highly long-term effective treatment for pathological health anxiety with long-term benefits. Standard care for health anxiety in medical clinics promotes depression. Nurse therapists are effective practitioners.